Budun dăkīma - Mahalēkama, Seneviratna (Koḷamba : Ăs. Goḍagē saha Sahōdarayō, 1992)
Characterization of the Buddha through his words and sayings.
In Sinhalese.
Keywords: Gautama Buddha; Gautama Buddha -- Teachings; Gautama Buddha; Teachings